Robotic surgery for simultaneous gastric and rectal cancers. Issue 2 (26th November 2022) - Ojima, Hitoshi; Yamada, Kazunosuke; Takada, Takahiro; Imaizumi, Jun; Suzuki, Masaki; Enokida, Yasuaki; Mochida, Yasushi; Kato, Ryuji
Abstract: The number of patients with multiple primary malignancies is increasing due to the improvements in diagnostic techniques, which increases the necessity of simultaneous resection. Meanwhile, minimally invasive robotic surgery is becoming popular in Japan, and its use in multiple cancer resection will increase. We present our experience with the settings and ports placement when using the da Vinci Xi system for simultaneous resection of rectal and gastric cancer.